2019
DOI: 10.1371/journal.pcbi.1007462
|View full text |Cite
|
Sign up to set email alerts
|

Simple models of quantitative firing phenotypes in hippocampal neurons: Comprehensive coverage of intrinsic diversity

Abstract: Patterns of periodic voltage spikes elicited by a neuron help define its dynamical identity. Experimentally recorded spike trains from various neurons show qualitatively distinguishable features such as delayed spiking, spiking with or without frequency adaptation, and intrinsic bursting. Moreover, the input-dependent responses of a neuron not only show different quantitative features, such as higher spike frequency for a stronger input current injection, but can also exhibit qualitatively different responses,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…Additionally, the presence of dark and light PENK granule cells may reflect the existence of different subsets of PENK granule cells. This idea would be consistent with recent demonstration of diverse molecular markers in granule cells (Hamilton et al, 2017; Venkadesh et al, 2019). The significance of this observation in light of sex differences in the expression of PENK in granule cells is a topic of future investigations.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the presence of dark and light PENK granule cells may reflect the existence of different subsets of PENK granule cells. This idea would be consistent with recent demonstration of diverse molecular markers in granule cells (Hamilton et al, 2017; Venkadesh et al, 2019). The significance of this observation in light of sex differences in the expression of PENK in granule cells is a topic of future investigations.…”
Section: Discussionsupporting
confidence: 90%
“…It was previously reported that bursting dynamics do not exist for low values of the parameter in the IM neuron (see eqn-1) [24]. We obtained doublet-and singlet-spiking neuron models by only varying parameter from the chaotic-spiking model ( =1.5; =175pA and =0.5; =200pA for doublet-and singlet-spiking neurons respectively) (Fig 3).…”
Section: IIImentioning
confidence: 83%
“…We noticed that existing Hippocampome.org information on membrane biophysics and firing patterns were all obtained in vitro from slice preparations. Given their relevance to inform computational models [ 30 ], we favor sharp intracellular recordings in vivo to complement these in vitro data. Thus, we obtained new data from cells in the DG ( n = 3 granule cells and a mossy cell) and CA3 region ( n = 7), as well as from GABAergic cells ( n = 2 PV basket cells).…”
Section: Resultsmentioning
confidence: 99%